15 | Monitoring and prevention of workplace violence against healthcare workers at the Catanzaro Provincial Health Authority - A. Sarcone; A. Gallucci; F. Lucia; V. Mendicino; C. Puntoriero; F. Lotito (Journal of Biological Research - Bollettino della Società Italiana di Biologia Sperimentale, 2026)
Background. In 2025, the Catanzaro Provincial Health Authority continued its surveillance of workplace violence against healthcare and social care professionals, in accordance with Italian Law No. 113/2020 and the recommendations of the National Observatory on the Safety of Healthcare and Social Care Professionals (ONSEPS). A standardized reporting procedure was implemented across all healthcare facilities to enhance staff competence in recognizing and managing violent incidents and to encourage prompt reporting of workplace aggression. Materials and Methods. Audits and investigative reviews were conducted to identify contributing and potentially preventable factors associated with reported incidents and to define appropriate corrective actions. Surveillance activities followed ONSEPS recommendations, and all collected data were transmitted through the official reporting system to the Regional Health Authority and the Italian Ministry of Health. Results. A total of 18 violent incidents were reported. Fourteen resulted in work-related injuries requiring medical leave. Incidents were equally distributed between male and female healthcare workers, with the highest frequency observed among individuals aged 40–49 years (n=8). By professional category, the cases involved 11 nurses, 4 physicians, 1 psychiatric rehabilitation therapist, and 2 healthcare assistants. Physical and verbal aggression occurred with equal frequency (9 cases each). Most incidents occurred on weekdays (n=12), with the night shift being the most affected. Aggressors were patients or service users in 12 cases and relatives or caregivers in 6 cases. The departments most frequently involved were the Psychiatric Inpatient Unit (Servizio Psichiatrico di Diagnosi e Cura, SPDC) and the Emergency Department, with 7 incidents each. Conclusions. The surveillance system remains active and supports the implementation of a corporate policy of zero tolerance toward physical and verbal violence against healthcare professionals. Continuous monitoring provides valuable information for identifying risk factors, strengthening preventive measures, and promoting a safer working environment.